Policy action plans for young entrepreneurs to increase economic water productivity in olive and milk value chains in Morocco - Amarasinghe, Upali; Ait El Mekki, Abdelkader; Amarnath, Giriraj (International Water Management Institute, 2024)
This report presents suggested action plans based on stakeholder consultations on investment and institutional strategies for assisting young entrepreneurs in increasing the economic water productivity, i.e., the value or profit of water consumed in the olive and milk value chains in Morocco. Key recommendations to implement in the short-term for a road map are: